Postpericardiotomy syndrome after cardiac surgery - Joonas Lehto; Tuomas Kiviniemi (TAYLOR & FRANCIS LTD, 2022)
Postpericardiotomy syndrome (PPS) is a well-known complication after cardiac surgery. The syndrome results in prolonged hospital stay, readmissions, and invasive interventions. Previous studies have reported inconsistent results concerning the incidence and risk factors for PPS due to the differences in the applied diagnostic criteria, study designs, patient populations, and procedure types. In recent prospective studies the reported incidences have been between 21 and 29% in adult cardiac surgery patients. However, it has been stated that most of the included diagnoses in the aforementioned studies would be clinically irrelevant. This challenges the specificity and usability of the currently recommended diagnostic criteria for PPS. Moreover, recent evidence suggests that PPS requiring invasive intervention such as the evacuation of pleural and/or pericardial effusion is associated with increased mortality. In the present review, we summarise the existing literature concerning the incidence, clinical features, diagnostic criteria, risk factors, management, and prognosis of PPS. We also propose novel approaches regarding to the definition and diagnosis of PPS.Key messages: Current diagnostic criteria of PPS should be reconsidered, and the analyses should be divided into subgroups according to the severity of the syndrome to achieve more clinically applicable and meaningful results in the future studies. In contrast with the previous presumption, severe PPS - defined as PPS requiring invasive interventions - was recently found to be associated with higher all-cause mortality during the first two years after cardiac surgery. The association with an increased mortality supports the use of relatively aggressive prophylactic methods to prevent PPS. The risk factors clearly increasing the occurrence of PPS are younger age, pleural incision, and valve and ascending aortic procedures when compared to CABG.